Qing`e Pill Inhibits Osteoblast Ferroptosis via ATM Serine/Threonine Kinase (ATM) and the PI3K/AKT Pathway in Primary Osteoporosis - Hao, Jian; Bei, Jiaxin; Li, Zhenhan; Han, Mingyuan; Ma, Boyuan; Ma, Pengyi; Zhou, Xianhu (Frontiers in Pharmacology, 2022)
Osteoporosis(OP) is an aging-related disease that always causes fragility fracture. Qing'e Pill is a mixture of Traditional Chinese Medicines (TCMs) and is composed of four herbs. It was reported the anti-osteoporosis function of Qing`e Pill, however, its mechanism is still unclear. In this study, several online databases were employed to obtain verified chemical molecules of Qing`e Pill and potential targets of Osteoporosis, such as gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG), Cytoscape, FerrDB Database, GeneCards (https://www.genecards.org/) and DisGeNET (https://www.disgenet.org/), TCMSP (https://www.tcmsp-e.com/) and BATMAN (http://bionet.ncpsb.org.cn/batman-tcm), STRING (https://cn.string-db.org/) and molecular docking. The potential key genes we got from the previous step were validated through the experiment in a human osteoblast cell line and Osteoporosis rat models through Western Blotting, RT-qPCR, ELISA, HE stain, Immunohistochemistry and immunofluorescence. Finally, molecular docking was used to predict the binding site and binding energy of key proteins with the drug molecule. The intersection targets of Qing`e Pill and Osteoporosis contained 121 proteins, whereas the target-pathway network included 156 pathways. We filtered 5 genes that stood out in the network pharmacology analysis for experimental verification as follow: ATM, PIK3CA, MAPK1, TLR4, TP53. The experiments validated that Qing`e Pill had therapeutic effects on Osteoporosis mainly via the inhibition of Ferroptosis and promoting cell survival through the PI3K/AKT pathway and Ataxia Telangiectasia Mutated (ATM). In conclusion, our study indicated the combining application of network pharmacology and experimental verification may provide an efficient method to validate the targets of Qing`e Pill on Osteoporosis.